Key Role of Multidisciplinary Collaboration towards Global Elimination of HCV Infection - Krekulova, Laura; Oktabec, Zbynek; Riley, Lee W (International journal of environmental research and public health, 2022)
The elimination of HCV (hepatitis C virus) infection is, according to WHO (World Health Organization), of international interest. With new diagnostic tools and treatment possibilities, one major challenge for the elimination is to involve infected patients, especially those from socially excluded subpopulations, into HCV infection-treatment programs. The key question is how to help people who inject drugs (PWID) to engage in HCV infection-treatment programs and improve communication between PWID and hepatologists or other medical professionals involved in the treatment of chronic HCV infection. Furthermore, the medical professionals have to accept the changing spectrum of patients with chronic viral hepatitis. Without close interdisciplinary cooperation, it would be extremely difficult to achieve the WHO goal of global viral hepatitis C elimination. Here, we try to encourage our colleagues as well as addictologists and social workers to play their crucial part in the viral hepatitis C eradication process. It is extremely important for the healthcare providers to be able to communicate with addicted clients, inform PWID about the latest developments in the diagnosis and HCV infection treatment, and get them motivated to engage with specialized treatment programs.
Keywords: intravenózní abúzus drog; Antiviral Agents; Světová zdravotnická organizace; Substance Abuse, Intravenous; lidé; Hepacivirus; hepatitida C; Hepatitis C; World Health Organization; antivirové látky; Humans